Potential of turmeric (Curcuma Longa Linn.) extract gel in the healing of perineal lacerations - Hidayah, Nurul; Supriyana, Supriyana; Mulyantoro, Donny Kristanto (Universitas Muhammadiyah Purwokerto, 2023)
Background: A perineal tear affects around 85% of women who give birth vaginally. Previous animal research has demonstrated the beneficial effects of turmeric extract gel on wound healing, which speeds up the process of repairing wounded tissue. However, since this research is only in vivo, more studies and clinical trials are required to evaluate the efficacy of using turmeric extract gel to treat perineal lacerations.Purpose: To analyze the potential of turmeric extract gel (Curcuma Longa Linn.) in reducing REEDA score and IL-6 levels in postpartum women.Method: This is a quasi-experiment study with pretest–posttest with control group design. The study respondents comprised 20 people in the intervention group who were given turmeric extract gel and amoxicillin and 20 in the control group who were given amoxicillin for seven days. Measurement of wound healing using the REEDA score while IL-6 levels using ELISA. Data analysis of used Friedman and Wilcoxon tests.Results: There was a significant decrease in the intervention group's REEDA score and IL-6 levels (p<0.05). There was a significant difference in the average decrease in REEDA score and IL-6 levels between the two groups (p<0.05). The administration of turmeric extract gel led to faster wound healing for two days compared to the control group, which was only given standard treatment.Conclusion: Turmeric extract gel can reduce REEDA score and IL-6 levels.